"Although Quite Nice, I Was Somehow Not Attracted by That Person": Attitudes Toward Romantically Committed Opposite-Sex Others Are Immune to Positive Evaluative Conditioning. (July 2013) - Koranyi, Nicolas; Gast, Anne; Rothermund, Klaus
Individuals who are motivated to find a romantic partner do not only have to detect desirable mating options but also have to prevent becoming committed to attractive but unpromising contacts. We thus propose that an acquisition of highly positive evaluations of already romantically committed opposite-sex others is prevented by self-regulatory processes. In two experiments, positive evaluative conditioning (EC) effects were obtained for facial photos (conditioned stimulus) of other opposite-sex singles when these pictures were paired with positive trait adjectives or odors (unconditioned stimulus). In line with our hypothesis, however, this positive EC effect did not obtain for faces of other persons who were presented as being already involved in a romantic relationship. The results demonstrate that the acquisition of positive attitudes during mate searching is modulated by self-regulatory processes that inhibit the emergence of futile commitments.